Analisa Dinding Geser Ditinjau dari Waktu Getar Alami dan Simpangan Antar Lantai - Yayan Adi Saputro; Khotibul Umam; Ana Rahmawati (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2020)
ABSTRACTFlat plate is a two-way plate system whose plate load is transferred directly to the column without passing through the beam structure. One of the advantages of this structure is that it can shorten the height of the building. However, the use of flat plate structures prone to lateral forces is mainly due to earthquake loads, because there are no beams causing weak joints (columns and plates), so the structure is flexible and can cause danger of failure to sliding. One alternative to increase structural rigidity is to use shear walls, where the shape and placement of the right layout are very influential. The research method is in the form of a 10-story building analysis using a flat plate structure system with 6 shear wall modeling. The distance between floors is 3 meters, with 4 x-axis ranges with a length of 6 meters and 3 stretches of the y-axis with a length of 5 meters. The function of the building as a flat is located in the city of Jepara with a medium land category. The analysis was carried out with the help of SAP2000 software in three dimensions (3D). Dynamic behavior reviewed includes natural vibration time and intersection between floors using spectrum response analysis methods. The results of the analysis show that the lowest time on natural vibration is found in modeling IV. For intersections between floors of all modeling meet SNI boundary requirements. The shear force increases in VI modeling for X direction and modeling III for direction Y. With the addition of lateral stiffening of the wall sliding on the flat plate structure system affects the internal forces on the corner, edge, and middle columns. From the dynamic behavior of the structure reviewed in modeling IV and VI, it presents the highest structural rigidity.